THE LEVEL OF WELL-BEING IN CHINESE UNIVERSITY EFL STUDENTS - Yang Lan; Mohd Rashid Saad, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aims at investigating the level of well-being (PERMA) in Chinese university EFL students. Adopting stratified random sampling, a questionnaire including 15-items is distributed to 518 EFL university students of thirteen universities in Gansu. Results show that respondents overall perceived a medium level of well-being. Finally, the study discusses the results according to each sub-construct and highlights the significance of well-being (PERMA) in Chinese university EFL students.